(untitled) (Can Tho, 2019)
This book introduce lto atomic structure and the periodic table, chemical bonding and molecular geometry, chemical thermodynamics, chemical kinetics, solution and colligative properties, chemical equilibrium...
Keywords: Hóa học,Chemistry